Bagaço do sorgo: estimativa de parâmetros cinéticos e pirólise analítica - Miranda, Mara Rúbia da Silva (2011)
Pyrolysis is currently the one of the most important technologies for transforming biomass into more useful products to society. Aiming to deepen the knowledge of the kinetics of pyrolysis, this study conducted an exploratory study of the decomposition of sorghum bagasse by thermogravimetry analysis (TG). The physicochemical characterization of sorghum bagasse was important to relate the composition of the major products of pyrolysis. The kinetics of decomposition was determined by dynamic tests, which were used the heating rates of 10, 20, 40 and 50 ° C / min. Three isoconversionals models according to Osawa, KAS and Starink were used to calculate the overall activation energy, adopting two size ranges of particles. The regressions obtained by these methods allowed to prove the change of reaction mechanism at high temperatures, confirming the release of heavier products. The results showed that the activation energy increases with particle size, leading to the conclusion that even with a small difference, there is an influence of particle size on heat transfer. The results of mass variation demonstrated the existence of two stages of mass loss, which are attributed to the majority decomposition of hemicellulose, cellulose and lignin. The model of independent parallel reactions (IPR) was also used to estimate the kinetic parameters for each of the reactions occurred. By using this model we observed that the higher the heating rate, the lower the activation energy. The results of the activation energy of the two tracks of particle size showed no significant differences, and the activation energy obtained by the method of IPR varied from 35.7 kJ / mol to 227.0 kJ / mol and for the isoconversionals models activation energy ranged from 127.9 kJ / mol to 159.7 kJ / mol. Another current analysis was the analytical pyrolysis, in which we observed the presence of two predominant compounds in pyrolysis conditions slow and fast pyrolysis (Benzofuran, 2,3-Dihydro and 2- Methoxy-4-Vinylfenol). The exploratory study of this dissertation allowed evaluating the potential of bagasse and biomass of sorghum in the processes of thermoconversion. Sorghum, especially the saccharine, which is currently being studied to complement the sugarcane in its off-season, may not only be used for ethanol production, but also as a source of biomass for other thermal conversion processes.